PLAIN OR ARCHAIC: THE NEW CZECH CIVIL CODE GOING AGAINST THE FLOW - KUBÁNEK, Michal; KLABAL, Ondřej (Comparative Legilinguistics, 2012)
The article presents the discussion on the wording of the new Civil Code of the Czech Republic which becomes effective on January 1, 2014. Some critics claim that the Code contains many newly coined or re-introduced terms which are unknown to the general public and may even feel archaic. Inspired by this debate, a survey was carried out in which a group of students was asked to assess the perceived familiarity with ten terms selected from the new Code and also mark the terms with respect to their perceived stylistic features. All the terms had been analysed with respect to their relative frequency in various text types using the Czech National Corpus. Only one term was assessed as known by more than 40% of the subjects. The same portion of the subjects marked six terms as archaic and five terms as strangely formed. The results show that the debate on the wording was justified. Nevertheless, the requirement for accessibility of legal documents to the general public should be seen with due consideration to various functions, situations and contexts in which individual genres and text types are used.